2018
DOI: 10.21315/tlsr2018.29.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Induction from Axillary Shoot Tip Explants of Fig (Ficus carica) cv. Japanese BTM 6

Abstract: Fig, or Ficus carica, is a fruit tree from the Moraceae family and is widely grown in tropical and subtropical regions of the world. Fig plants are mainly propagated through grafting, air layering, and hardwood cutting whereby these methods were found to be less efficient. Plant tissue culture is efficient method to propagate plants, particularly to produce true-to-type platelets for mass multiplication. The aim of this study is to induce multiple shoot formation on Ficus carica cv. Japanese BTM 6 through iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…In Chlorophytum borivilianum, BAP (2.0~6.0 mg/L) leads to a significant increase in shoot multiplication, and kinetin (2.0~6.0 mg/L) significantly increases shoot elongation (Ashraf et al 2014). In Ficus carica, BAP is more effective for multiple shoot induction from shoot tip explants as compared to zeatin and its optimum concentration was 2 mg/L (Ling et al 2018). In Scutellaria alpine, a comparison of BAP, kinetin, zeatin, and TDZ, found that BAP (0.5~1.0 mg/L) was the most effective for multiple shoot induction from shoot tip explants (Grzegorczyk-Karolak et al 2015).…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…In Chlorophytum borivilianum, BAP (2.0~6.0 mg/L) leads to a significant increase in shoot multiplication, and kinetin (2.0~6.0 mg/L) significantly increases shoot elongation (Ashraf et al 2014). In Ficus carica, BAP is more effective for multiple shoot induction from shoot tip explants as compared to zeatin and its optimum concentration was 2 mg/L (Ling et al 2018). In Scutellaria alpine, a comparison of BAP, kinetin, zeatin, and TDZ, found that BAP (0.5~1.0 mg/L) was the most effective for multiple shoot induction from shoot tip explants (Grzegorczyk-Karolak et al 2015).…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…Penelitian terdahulu tentang induksi kalus tanaman Tin, diantaranya dilakukan dengan menggunakan kombinasi IBA dan Kinetin (Fadilah et al, 2014), BAP dan Zeatin (Ling et al, 2018). Penelitian ini menggunakan kombinasi BAP dengan air kelapa untuk morfogenesis tunas, dan BAP dengan 2,4-D untuk induksi kalus.…”
Section: Pendahuluanunclassified
“…Hasil pengamatan jumlah daun dan panjang tunas menunjukkan nilai yang baik dan selaras pada perlakuan BAP 2 mg/L + air kelapa 100 mL/L (Tabel 2). Perlakuan tunggal BAP dengan konsentrasi 2 mg/L pada penelitian Ling et al (2018), juga menunjukkan jumlah tunas dan panjang tunas tanaman Tin yang paling baik.…”
Section: Hasil Dan Pembahasan Morfogenesis Tunas Tanaman Tinunclassified
“…It is also contain high energy and nutrients, especially P, K, Ca, Mg, and Fe [1]. In addition, figs contain much of fiber which is higher than bananas, grapes, strawberries, apples, and oranges [2]. Figs can be consumed freshly or dried, but fresh figs are perishable and must be eaten or processed immediately.…”
Section: Introductionmentioning
confidence: 99%
“…The problem on conventional propagation such as grafting is require a lot of planting materials, which can cause problems if it is necessary to produce high quality seeds in large quantities. In addition, conventional vegetative propagation does not produce consistent plant growth, which will result in inconsistent fruit production, especially for largescale markets [2]. Micropropagation/micro propagation by tissue culture techniques, also known as in vitro regeneration, is an alternative method that can be used to multiply plants efficiently.…”
Section: Introductionmentioning
confidence: 99%